Calculation of Magnetostrictive Vibration of Four-Node Iron-Core Unit Based on Magnetic Network Method - Zhang, Huiying; An, Jiabao; Tian, Mingxing; Gu, Shengjie; He, Shouhu; Wang, Tiange (Archives of Electrical Engineering (Online), 2025)
At present, the analysis of iron core vibration often uses the finite element method, but its modeling process is complex and the calculation time is long. To address this issue, this paper proposes a magnetic mechanical coupled magnetostrictive vibration calculation model for iron cores based on the magnetic network method with four-node elements, intended to achieve fast and accurate vibration assessment. Taking the Epstein square circle as the research object, a four-node element magneto-mechanical coupling model of the square circle was constructed. The calculation results were compared with the finite element simulation results at typical positions of the square circle, and the consistency of the magnetic flux density values and node displacements was good, verifying the effectiveness and accuracy of the proposed method. The comparison of simulation time shows that the four-node magneto-mechanical model significantly shortens the calculation time when calculating vibration displacement, providing new ideas and feasible methods for efficient calculation of iron core vibration and noise in electrical equipment.